Pidana Kerja Sosial sebagai Alternatif Pemidanaan dalam Perspektif Penologi dan Sistem Penitensier Indonesia - Uci Febriani; Bella Ananda Sari; Muhammad Edwar; Ria Anggraeni Utami (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
This study aims to examine community service punishment as an alternative sentencing in the perspective of penology and the Indonesian penitentiary system and to analyze the legal position of community service punishment within the Indonesian criminal sentencing system under the new Criminal Code. This research uses a normative legal research method with statutory and conceptual approaches. The data used are secondary data consisting of primary, secondary, and tertiary legal materials obtained through library research and analyzed qualitatively. The results show that community service punishment in the new Criminal Code has the position as a principal punishment that serves as an alternative to short-term imprisonment and fines and is categorized as a non-custodial sentence. From the perspective of penology, community service punishment reflects rehabilitative, reintegrative, and restorative justice-oriented sentencing. In the correctional system, community service punishment can be a solution to prison overcrowding and supports the correctional objective of rehabilitation and social reintegration of offenders. However, its implementation still requires technical regulations, supervision mechanisms, and institutional readiness to ensure effective application within the Indonesian criminal justice system.